Cerebral Venous Thrombosis in Pediatric Age: Risk Factors and Prognosis - Pais-Cunha, Inês; Almeida, Ana I.; Curval, Ana R.; Fonseca, Jacinta; Melo, Cláudia; Sampaio, Mafalda; Sousa, Raquel (Neuropediatrics, 2024)
Introduction Cerebral venous thrombosis (CVT) is a rare but potentially fatal disease in pediatric age with an important morbimortality. In adults several factors have been associated with worse outcomes, however there are still few studies in children. This study aims to identify risk factors associated with clinical manifestations and long-term sequelae in pediatric CVT.Methods Retrospective analysis of pediatric inpatients admitted to a tertiary-care hospital due to CVT between 2008 and 2020.Results Fifty-four children were included, 56% male, median age of 6.5 years (9 months–17.3 years). Permanent risk factors were identified in 13 patients (malignancy, 8; hematologic condition, 5) and transient risk factors in 47, including head and neck infections (57%) and head trauma (15%). Multiple venous sinuses involvement was present in 65% and the deep venous system was affected in four patients. Seventeen percent had intracranial hemorrhage and 9% cerebral infarction. Sixty-four percent of patients with multiple venous sinuses involvement presented with severe clinical manifestations: impaired consciousness, intracranial hypertension, acute symptomatic seizures or focal deficits. Regarding long-term prognosis, six patients had major sequelae: epilepsy (n = 3), sensory motor deficits (n = 2), and cognitive impairment (n = 3). Permanent risk factors were associated with severe clinical manifestations (p = 0.043). Cerebral infarction and intracranial hemorrhage were associated with major sequelae (p = 0.006 and p = 0.03, respectively, adjusted for age and sex).Conclusion Permanent risk factors, involvement of multiple venous sinuses, intracranial hemorrhage, and cerebral infarction, were related to worse prognosis. Detection and early management of risk factors may limit CVT extension and reduce its morbimortality.
Keywords: intracranial thrombosis; venous thrombosis; pediatrics; cerebral infarction; cerebral hemorrhage